2005
DOI: 10.4049/jimmunol.175.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD8+CD25+ T Lymphocytes from MHC Class II-Deficient Mice Exhibit Regulatory Activity

Abstract: We characterized CD8+ T cells constitutively expressing CD25 in mice lacking the expression of MHC class II molecules. We showed that these cells are present not only in the periphery but also in the thymus. Like CD4+CD25+ T cells, CD8+CD25+ T cells appear late in the periphery during ontogeny. Peripheral CD8+CD25+ T cells from MHC class II-deficient mice also share phenotypic and functional features with regulatory CD4+CD25+ T cells: in particular, they strongly express glucocorticoid-induced TNFR family-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 42 publications
5
79
1
Order By: Relevance
“…Interestingly, a CD8 1 Foxp3 1 population expands in MHCclass-II-deficient mice and shares phenotypic and functional features with CD4 1 CD25 1 Tregs [37], whereas the absence of CD8 1 Foxp3 1 T cells in MHC-class-I-deficient mice suggests MHCI restriction [25]. The presence of Foxp3 1 cells among CD8SP thymocytes suggests at least a partial thymic origin of CD8 1 Foxp3 1 T cells, similar to CD4 1 Foxp3 1 Tregs [18], although re-immigration into the thymus after peripheral conversion cannot be formally excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a CD8 1 Foxp3 1 population expands in MHCclass-II-deficient mice and shares phenotypic and functional features with CD4 1 CD25 1 Tregs [37], whereas the absence of CD8 1 Foxp3 1 T cells in MHC-class-I-deficient mice suggests MHCI restriction [25]. The presence of Foxp3 1 cells among CD8SP thymocytes suggests at least a partial thymic origin of CD8 1 Foxp3 1 T cells, similar to CD4 1 Foxp3 1 Tregs [18], although re-immigration into the thymus after peripheral conversion cannot be formally excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have indicated that a unique subset of CD4 ϩ CD8 ϩ CD25 ϩ T cells in MHC II Ϫ/Ϫ mice is enriched in FoxP3 mRNA and capable of suppressing T cellmediated inflammatory bowel disease (21). Curiously, while prevalent in MHC II Ϫ/Ϫ mice, CD8 ϩ CD25 ϩ T cells are quite rare in wild-type animals (20). Cellular Immunology Section, Laboratory of Immunology, National Institute of Allergy and Infectious Diseases, National Institutes of Health, Bethesda, MD 20892 In this study, we present a comprehensive investigation of the development and phenotype of FoxP3 ϩ T cells in relation to the expression of conventional MHC molecules.…”
Section: Foxp3mentioning
confidence: 99%
“…Although the majority of FoxP3 ϩ cells in wildtype mice appear to require MHC class II expression for their thymic development, subsets of FoxP3 ϩ CD8 ϩ T cells are present in the thymus of both wild-type and MHC class II-deficient (MHC II Ϫ/Ϫ ) mice (19). Furthermore, the periphery of MHC II Ϫ/Ϫ mice contains CD8 ϩ CD25 ϩ T cells that exhibit contact-dependent suppressive activity analogous to that mediated by wild-type CD4 ϩ CD25 ϩ T cells (20). Other reports have indicated that a unique subset of CD4 ϩ CD8 ϩ CD25 ϩ T cells in MHC II Ϫ/Ϫ mice is enriched in FoxP3 mRNA and capable of suppressing T cellmediated inflammatory bowel disease (21).…”
Section: Foxp3mentioning
confidence: 99%
“…Such Treg cells have been shown to need for their survival in the periphery the presence of the respective self-antigen (7). Besides these most prominent CD4 ϩ CD25 ϩ Treg cells, CD8 ϩ T cells have also been reported to be involved in the control of T cell responses (8)(9)(10)(11)(12)(13)(14)(15). However, such CD8…”
mentioning
confidence: 99%